Predictors of unplanned hospital readmissions and emergency department revisits in patients with acute ischemic stroke - Jumah, Ammar; Ro, Jennifer; Ma, Tianwen; Owens, Javacia; Wu, Yunong; Starnes, Danielle; Christopher, Hannah; Blanke, Debra; Henriquez, Laura; Belagaje, Samir R.; Kvantaliani, Nino; Cabral, Jacquelyn; et al. (Frontiers in Neurology, 2025)
ObjectivesWe aim to identify factors associated with emergency department (ED) revisits and hospital readmissions after acute ischemic stroke (AIS) diagnosis and to determine if early outpatient follow-up can reduce readmissions.MethodsWe retrospectively identified all AIS patients discharged from a hospital network, from October 1, 2022 to March 31, 2024. Baseline characteristics, inpatient metrics and post-discharge outpatient follow-up were assessed to identify factors associated with ED revisits and readmissions to the healthcare system within 90-days.ResultsOf 1,973 patients, 464 (23.5%) had ED visits within 90 days and 263 (13.3%) had hospital readmission within 90 days. The median age was 68 [IQR 58, 77]. In multiple logistic regression analyses, factors independently associated with 90-day ED visit were history of heart failure (HF) (OR 1.46, 95% CI 1.11–1.93; p = 0.007), diabetes mellitus (DM) (OR 1.41, 95% CI 1.12–1.77; p = 0.003), atrial fibrillation (AF) (OR 1.47, 95% CI 1.13–1.92, p = 0.004) and an increasing Charlson comorbidity index (CCI) score (OR 1.10, 95% CI 1.03–1.18), p = 0.003). Factors associated with 90-day readmission were HF (OR 1.51, 95% CI 1.08–2.11, p = 0.015), DM (OR 1.50, 95% CI 1.13–2.01, p = 0.006), AF (OR 1.40, 95% CI 1.00–1.94, p = 0.047) and increasing CCI score (OR 1.12, 95% CI 1.03–1.21, p = 0.006). Discharge to inpatient rehabilitation or skilled nursing facility (vs. home or home health) were associated with 90-day ED revisits and hospital readmissions. Patients who completed early (<30 days) outpatient stroke clinic follow-up had a lower likelihood of 90-day readmission (OR 0.68, 95% CI 0.52–0.90; p = 0.006).ConclusionPatients with certain comorbidities including HF, DM, AF and those with a higher CCI score have a higher likelihood of a 90-day ED revisit and hospital readmission. Unplanned hospital readmissions may be preventable with early outpatient visits in a dedicated stroke clinic after discharge for AIS patients.